Da produção aos mercados agroalimentares: dinâmicas de agricultores inseridos em cadeias curtas de comercialização - Camara, Simone Bueno (2020)
Agricultural markets have been participating in the development of economies since the dawn of civilizations, ranging from simple exchanges to more complex negotiations. Among these short supply channel that seek to shorten the distances between farmer and consumer seeking to shorten the distance between the farmer and the consumer causing an approximation between the place where it is producing and consuming making a “fairer” relationship for farmers and consumers. Thus, this study aims to analyze the dynamics of production and marketing used by farmers who access markets through short agrifood chains in the extreme region north Rio Grande do Sul. Also, were interviewed the total of 31 farmers of the municipalities of Alpestre, Ametista do Sul, Iraí and Planalto, between the months of October and November 2019. The means to operationalize the research consists of three stages of analysis. The first is to measure the participation of marketing channels in the composition of farmers’ incomes farmers inserted in short supply channel, using as method of analysis the methodological framework of production systems. The first finding is the existence of three productive systems. In this case: vegetable and systems the combination of local and global markets occur. the largest income chains short are found in agro-industrial systems and alternative systems. The next question is to understand the capacity of socioeconomic reproduction in the productive units based on short chain income. In this stage of analysis income from short chains is stratified and grouping by salary class. Income from short chains allows socioeconomic reproduction only when earning more than four minimum wages. In other salary strata, only with the complementation of rents from global and alternative markets, as well as other income, it is possible to obtain the capacity for socioeconomic reproduction. The third step is to analyze the efficiency of short food supply channel in the different production systems found. For data collection and analysis, a structured script was developed based on Belletti e Marescotti “L’innovazione economica della filiera corta”. The system that presented the highest efficiency rates in five of the six variables analyzed was the vegetable agroindustrial, that has completion of production. The conventional systems, be mixed like vegetable, are those with the lowest efficiency rates, due to the fact that productions destined for short chains are complementary to income and most of them, products with low added value. In general, it is observed that short chains are an alternative market for families that seek productive autonomy, diversify income or dispose of surplus production. Although, this channel also needs specialization when used as themain source of income, likewise only the commercialization of fresh production does not make it efficient in different aspects. However, these results should not be generalized, given the specificity of the region under analysis and the complexity of the theme, therefore, new analyzes in other regions / farmers are essential.